STUDENTS' FOREIGN LANGUAGE CLASSROOM ANXIETY (FLCA) IN EFL CLASSROOM : IT'S LEVELS, SOURCES AND COPING STRATEGIES A Case Study in A State University In Bandung) - Muhtar, Siti Nuraeni (2014)
This study reports students' foreign language anxiety in EFL classroom at university level. It investigates students' foreign language anxiety levels, their sources of anxiety and their coping strategies. This study employed a qualitative research design, embracing the characteristics of a case study. Three kinds of instruments were applied for this study: observation, questionnaires (adapted from Foreign Language Classroom Anxiety Scale by Horwitz) and semi structured interview. The data were collected by means audio and video recording to capture students' sources of anxiety and their coping strategies. It was collaborated with semi structured interview. Those data were transcribed and coded by using the categorization from Alwasilahs' coding strategy (2002). The data were also obtained by quantifying questionnaires in order to know students anxiety level. The first finding reveals that the students who experience moderate level of anxiety have the highest percentage (37,14%), while those who experience low level of anxiety have the lower of percentage than the moderate (34,28%). Meanwhile, the students with high level of anxiety have the lowest percentage (28,58%). Secondly, the sources of students' language anxiety is communication apprehension (41,52 %). Meanwhile, test anxiety has the lower percentage than communication apprehension (32,81 %). The last source, fear of negative evaluation, has the lowest percentage among the other sources (25,67). Lastly, the most common coping strategies exhibited by the participants of this study were the flight behaviors such as avoidance, rationalization and withdrawal. Relating to compromise behavior, this kind of defense mechanism can be viewed in this study was only in anticipation behavior. In contrast, aggressive behaviors (displacement, cynicism or negativity, interrogation, and acting out) were not observed. Only competition which specifically means the effort to demonstrate superiority either in front of their friends or their lecturer in order to avoid a negative evaluation of overall incompetence. The result implies that language anxiety is not only situation-specific in that its level can differ from one situation to another, but also response-specific in that its level can vary depending on what defense mechanism has been employed and what kind of sources they have. Additionally, it can be stated that interaction between language anxiety and defense mechanisms employed is an on-going process. Based on the results of this study, the researcher reveals some limitations and proposes some recommendations for English teachers and others who are concerned with English education, especially on EFL subject. Keywords: Foreign Language Classroom Anxiety, Levels, Sources, Coping Strategies, University Students.